The role of statistics in supporting economic decision-making (a field study in Iraqi banks) - Maab Adil Sabbar, Maab Adil Sabbar (The Gulf Economist, 2025)
This study analyzes the role of statistical methods in supporting economic decision-making in Iraqi banks, focusing on data quality, efficiency of statistical programs, and analysis time. The results revealed a strong correlation between the use of statistical methods and the quality of decisions (Pearson = 0.737), with data quality being the most influential factor, while limited staff and weak software posed obstacles. The study recommends improving information infrastructure, training staff, and enhancing data quality to accelerate processing and strengthen decision-making.